(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Emotional intelligence (EI) has been an important and controversial topic over the past few decades. Due to its importance and its association with many areas of life, it has made it the subject of expert study. Emotional intelligence is the drive to feel, think, learn, solve problems, make decisions, and control and manage emotions again. In this article, the researcher attempts to investigate the relationship between emotional intelligence and self-esteem among ordinary students at the Faculty of Arts at the University of Tripoli, Libya. The researcher applied two scales, one for emotional intelligence and the other for self-esteem. The results of this current study are in agreement with the results of previous studies discussed by the researcher in this study. At the end of the study, the researcher recommended several recommendations.